2001
DOI: 10.1016/s0378-1135(01)00360-1
|View full text |Cite
|
Sign up to set email alerts
|

Necrotoxigenic Escherichia coli type-2 invade and cause diarrhoea during experimental infection in colostrum-restricted newborn calves

Abstract: There exists experimental evidence that necrotoxigenic Escherichia coli (NTEC) strains producing the cytotoxic necrotising factor 1 cause intestinal and extra-intestinal disease in piglets. On the other hand, no experimental model has been developed with NTEC strains producing the cytotoxic necrotising factor 2. In all, 14 colostrum-restricted calves were orally challenged with two strains isolated from the faeces of a diarrheic calf (B20a) or from the heart blood of a septicaemic calf (1404). All calves had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
17
1
1
Order By: Relevance
“…They are also widely distributed in healthy cattle and calves [37 -40]. Experimental infections of calves with NTEC-2 have shown that these bacteria are able to colonize the intestine and enter the bloodstream, but their potential to cause clinical symptoms strongly depends on the hosts immune status, and NTEC-2 thus are supposed to be opportunistic pathogens [5]. We were not able to identify genes coding for both ColV-and Vir-plasmid-determinants which is in accordance with other studies on bovine O78 strains [9,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also widely distributed in healthy cattle and calves [37 -40]. Experimental infections of calves with NTEC-2 have shown that these bacteria are able to colonize the intestine and enter the bloodstream, but their potential to cause clinical symptoms strongly depends on the hosts immune status, and NTEC-2 thus are supposed to be opportunistic pathogens [5]. We were not able to identify genes coding for both ColV-and Vir-plasmid-determinants which is in accordance with other studies on bovine O78 strains [9,41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, also necrotoxigenic E. coli (NTEC) gained more attention in diarrheagenic infections in cattle [5,6]. In humans, however, during the last decade, other E. coli pathotypes associated with diarrhea have been increasingly identified, namely enteroinvasive (EIEC), diffuse adhering (DAEC), enteroaggregative (EAEC), and certain necrotoxigenic (NTEC) E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…The role of CNF-producing E. coli strains in diarrheal diseases has not been defined. Recently, Van Bost et al (2001b) reported that CNF2-producing strains were able to colonize the intestines, cause long-lasting diarrhea, and invade the blood stream of newborn colostrum-restricted calves after experimental inoculation through the oral route. A previous report on the experimental infection of germfree colostrum-deprived newborn piglets showed no evidence for a pathogenic role of CNF1 in the development of diarrhea (Fournout et al 2000).…”
mentioning
confidence: 99%
“…CNF2-producing strains have been isolated from calves and lambs with diarrhoea or bacteraemia, or both [40]. Experimental inoculation of an E. coli strain with proven CNF2 toxin expression into colostrum-restricted newborn calves resulted in intestinal colonisation, causing long-lasting diarrhoea and bacteraemia with localisation in various internal organs [41].…”
Section: Discussionmentioning
confidence: 99%